2020
DOI: 10.3928/1081597x-20200120-01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capsular Tension Ring Implantation on Postoperative Rotational Stability of a Toric Intraocular Lens

Abstract: PURPOSE: To analyze clinical outcomes of cataract surgery with implantation of a toric intraocular lens (IOL) and to evaluate the effect of capsular tension ring (CTR) presence or absence on the rotational stability of implanted IOLs and postoperative refraction. METHODS: This cohort study included 64 eyes of 41 patients who underwent uneventful cataract surgery with implantation of a toric IOL (enVista toric MX60T; Bausch & Lomb, Rochester, NY) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4 , 9 , 10 , 12 , 17–19 confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5 , 9 , 18 , 20–24 the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25 , 26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°). 18 …”
Section: Discussionsupporting
confidence: 67%
“…Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4 , 9 , 10 , 12 , 17–19 confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5 , 9 , 18 , 20–24 the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25 , 26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°). 18 …”
Section: Discussionsupporting
confidence: 67%
“…15 Initial rotational rates (>5°) for this IOL have ranged from 9.5% to 23%. 11,16,17 One study compared rotational rates of the enVista Toric (n=21) to the AcrySof ® IQ Toric (n=28) (Alcon Vision LLC, Fort Worth, TX), and Lentis LT (n=14) (Oculentis, Berlin, Germany); rotation ≥5° occurred in 9.5%, 35.7%, and 35.4%, respectively. The enVista Toric IOL was found to be the most rotationally stable of the three; however, the study was small and statistical significance was not reported for these specific findings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for eyes with high myopia, plate-haptic IOLs may be a preferred option, especially when premium IOLs are used. In addition, if necessary, a capsular tension ring (CTR) can be used in highly myopic patients to assist IOL centration and reduce postoperative IOL rotation [ 30 ]. Anterior segment enlargement verified herein confirms the findings of several large cross-sectional studies, in which anterior chamber depth correlated positively with AL [ 13 , 31 ].…”
Section: Discussionmentioning
confidence: 99%